Comparing telehealth with office-based visits for common pediatric otolaryngology complaints. (June 2021) - Kolb, Caroline M.; Born, Kristen; Banker, Karen; Barth, Patrick; Aaronson, Nicole L.
Abstract: Objective: The objective of this study was to evaluate the feasibility of telehealth visits and compare office-based visits for pediatric patients undergoing evaluation of recurrent acute otitis media or sleep-disordered breathing. Methods: A retrospective cohort study compared telehealth patients with matched controls seen in the office. The feasibility of a thorough patient evaluation in a single telehealth visit without a follow-up office visit was assessed. Both groups were also compared for completeness of physical exam, management, follow-up recommendations, and correlation of physical exam findings with intraoperative findings. Results: 100 children [mean age (SD) = 20.7 (15.6) months] with a chief complaint of recurrent acute otitis media and 128 children [5.4 (3.2) years] with a chief complaint of sleep-disordered breathing were evaluated. Recommendations for surgery, additional studies, or routine follow-up were similar between telehealth and office-based groups. Physical exam feasibility was significantly different for the nasal cavity, oropharynx, and middle ear ( P  < .001). Patients who underwent office-based consultation were much more likely to have findings of middle ear fluid at the time of tympanostomy tube placement (79.3% vs 39.3%, P  = .002). There was no significant difference between preoperative and intraoperative tonsil size discrepancies ( P  = .749). Conclusion: Telehealth can be used successfully for the evaluation of pediatric patients with sleep-disordered breathing; however, reliance on history alone may result in unnecessary tympanostomy tube placement in patients with recurrent acute otitis media. Physical examination of the oropharynx, nasal cavity, and middle ear via telehealth presents a unique challenge in pediatric otolaryngology. Highlights: Office and telehealth visits have differences in physical exam completeness. Telehealth patients had a lower likelihood of middle ear fluid at the time of BMT. Telehealth appears effective in assessing children with sleep-disordered breathing. Telehealth may result in unneeded surgery in patients with recurrent ear infections.